Trends and Associations of Chilblains Prevalence with Connective Tissue Diseases, Including COVID-19 Incidence - Argobi Y (Clinical, Cosmetic and Investigational Dermatology, 2025)
Yahya Argobi1,2 1Dermatology Department, King Khalid University, Abha, Saudi Arabia; 2Dermatology Department, Massachusetts General Hospital, Boston, MA, USACorrespondence: Yahya Argobi, Al-Gara’a, College of Medicine, Abha, 62529, Saudi Arabia, Email yahya.derm@gmail.comBackground: Chillblains, also known as perniosis, are inflammatory skin lesions that have long been associated with exposure to low temperatures. However, their co-occurrence with autoimmune illnesses and viral infections, particularly COVID-19, has received increased attention. This study was designed to examine chilblains’ documented prevalence and association with autoimmune diseases and COVID-19.Methods: This was a descriptive cross-sectional study carried out at Mass General Brigham (MGB), an extensive integrated healthcare system situated in Greater Boston, Massachusetts. The study included patients with a confirmed diagnosis of chilblains from 2014 to 2021 and COVID-19 from 2020 to 2021. The study was approved by the Mass General Brigham Human Research Committee, ensuring compliance with ethical standards.Results: During the study, 24,711 charts were reviewed, identifying 1478 patients with chilblains, resulting in an overall registered prevalence of 0.02463%. The majority of chilblains patients were female (72.5%), with the highest proportion in the 31– 30-year age group (31.3%). 169 (11.43%) patients were identified with autoimmune diseases, predominantly females (94.1%). The most prevalent condition among them was systemic lupus erythematosus (SLE) (52.6%). Among COVID-19-positive patients (n = 88,763), 30 were diagnosed with chilblains, leading to a prevalence of 0.033%. Females (66.7%) and individuals aged 40– 50 (56.7%) were predominantly affected.Conclusion: This study found a low prevalence primarily among young females and a significant correlation with connective tissue disorders like SLE. The study also notes a rare occurrence of chilblains in COVID-19 patients, suggesting a possible association that requires further investigation, particularly regarding demographic patterns within this subgroup.Keywords: chilblains, autoimmune diseases, COVID-19, prevalence, connective tissue disorders, SLE